Evaluation of Apical Extrusion of Debris with Tactile Controlled Activation Technique Using Controlled Memory Files in Curved Root Canals: An in vitro Study - Drisya D. Nambiar; Gurudutt Nayak; A. R. Vivekananda Pai; Ojaswini Pawar; Sonam Bohra; Gopal C. Sanyal; Mudassir Khan (Journal of Pharmacy and Bioallied Sciences)
Background and Objectives: The purpose of the study was to quantify the amount of debris that was extruded apically when single-length and tactile controlled activation (TCA) techniques were used to instrument curved canals. Materials and Methods: A total of forty mandibular first molars having curved mesial roots of standardized length were subjected to instrumentation, utilizing both single-length and TCA techniques. Pre-weighed Eppendorf tubes were used to collect the extruded debris. The tubes underwent weighing to acquire the final weight of the dry debris. The initial weight was subtracted from the final weight to determine the weight of the extruded debris. The Shapiro–Wilk test was utilized to evaluate the data distribution. The Mann–Whitney U test was utilized to analyze continuous variables with a significance level of P ≤ 0.05. Results: Either of the techniques tested was associated with apical debris extrusion, but the TCA technique in a crown-down approach resulted in considerably less debris extrusion compared to the single-length technique. Conclusion: The TCA technique in the crown-down approach demonstrated the least debris extrusion, suggesting the importance of selecting the appropriate technique in curved canal management.